PENGUKURAN KINERJA DENGAN PENDEKATAN BALANCED SCORECARD PADA BALAI KONSERVASI SUMBER DAYA ALAM NUSA TENGGARA BARAT TAHUN 2010 - 2012 - , Wihandono Eki Sutopo; , Dr. Wahyu Widayat, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to measure the performance of the Nature Resources Conservation Office of West Nusa Tenggara with the Balanced Scorecard approach, which includes a financial perspective, customer perspective, internal process and learning and growth perspective. Comparing the results of performance measurement Nature Resources Conservation Office West Nusa Tenggara with the Balanced Scorecard approach to performance measurement results that have been there before. The data used in this study is primary data and secondary data in the form of questionnaires. The analytical tool used in this study is the Balanced Scorecard. The analysis showed that the performance measurement results from a financial perspective is very good for 2010, 2011 and is good for 2012. Performance measurement from the perspective of the customer using the customer satisfaction level indicators covering aspects of tangibles, reliability, responsiveness, assurance and empathy. The measurement results showed that the respondents were very satisfied with each of these aspects. Performance of the internal process perspective is measured using indicators of innovation, shows that the overall performance of the internal process perspective is satisfied. The performance of the learning and growth perspective is composed of three aspects : employee satisfaction, motivation and empowerment of employees, and the ability of information systems. Respondents responded quite satisfied with each of these aspects, so that the overall performance of the learning and growth perspective is quite satisfied. The overall results of performance measurement of the Nature Resources Conservation Office of West Nusa Tenggara with the Balanced Scorecard approach that includes a financial perspective, customer perspective, internal process and learning and growth perspective is good, while the performance of the Nature Resources Conservation Office of West Nusa Tenggara realization approach is very good for 2010, 2011 and is good for the year 2012.